Merothripidae from Malaysia: Merothrips with one new species and two new species records - Ng, Y.f.; Mound, L.a. (Zootaxa, 2018)
The family Merothripidae is recorded for the first time from Malaysia. Three species of Merothrips, the largest genus in the family, are recorded here, with the description of Merothrips yii sp.n.